2015
DOI: 10.1002/bies.201500018
|View full text |Cite
|
Sign up to set email alerts
|

A guide to the field of palaeo colour

Abstract: Melanin, and other pigments have recently been shown to preserve over geologic time scales, and are found in several different organisms. This opens up the possibility of inferring colours and colour patterns ranging from invertebrates to feathered dinosaurs and mammals. An emerging discipline is palaeo colour: colour plays an important role in display and camouflage as well as in integumental strengthening and protection, which makes possible the hitherto difficult task of doing inferences about past ecologie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
120
1
6

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
2
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 98 publications
(132 citation statements)
references
References 108 publications
5
120
1
6
Order By: Relevance
“…The light portions, were markedly preserved as imprintation. Those structures were previously interpreted as autolithified bacteria (Wuttke, 1983;Davis & Briggs, 1995), but subsequent studies revealed them as evidence of fossilized melanosomes (Vinther et al 2008;Zhang et al, 2010;Barden et al, 2011;Glass et al, 2012;2013;McNamara et al, 2013;Vitek et al, 2013;Barden et al, 2014;Li et al, 2014;Egerton et al, 2015;Vinther, 2015). This interpretation, enabled reconstructions of ancient color patterns of extinct animals, such as dinosaurs, birds, reptiles and fishes.…”
Section: Future Perspectivesmentioning
confidence: 94%
“…The light portions, were markedly preserved as imprintation. Those structures were previously interpreted as autolithified bacteria (Wuttke, 1983;Davis & Briggs, 1995), but subsequent studies revealed them as evidence of fossilized melanosomes (Vinther et al 2008;Zhang et al, 2010;Barden et al, 2011;Glass et al, 2012;2013;McNamara et al, 2013;Vitek et al, 2013;Barden et al, 2014;Li et al, 2014;Egerton et al, 2015;Vinther, 2015). This interpretation, enabled reconstructions of ancient color patterns of extinct animals, such as dinosaurs, birds, reptiles and fishes.…”
Section: Future Perspectivesmentioning
confidence: 94%
“…The light portions, were markedly preserved as imprintation. Those structures were previously interpreted as autolithified bacteria (Wuttke, 1983;Davis & Briggs, 1995), but subsequent studies revealed them as evidence of fossilized melanosomes (Vinther et al 2008;Zhang et al, 2010;Barden et al, 2011;Glass et al, 2012;2013;McNamara et al, 2013;Vitek et al, 2013;Barden et al, 2014;Li et al, 2014;Egerton et al, 2015;Vinther, 2015). This interpretation, enabled reconstructions of ancient color patterns of extinct animals, such as dinosaurs, birds, reptiles and fishes.…”
Section: Future Perspectivesmentioning
confidence: 94%
“…An example of this in the present context is the use of synchrotron X-ray fluorescence and X-ray absorption techniques, which are capable of detecting trace metals (organically chelated copper) associated with melanins (Bergmann et al 2012) even after the melanosomes have been lost to dissolution. The problem is that organically chelated copper is not diagnostic of melanin, as other organic compounds common in nature (such as porphyrins which are common in feathers) are also capable of chelating copper (Vinther 2015).…”
Section: Epistemic Access To the Past: The Colors Of The Dinosaursmentioning
confidence: 99%